Application Of Project-Based Learning In College English Teaching - Sun, Bo; Xu, Rong; Weng, Zhengqiu; Wu, Bing (Journal of Theory and Practice of Humanities Science, 2023)
With the improvement of economic level, Internet technology has achieved relatively rapid development, and more emerging concepts have been applied to university teaching. In this case, project-based teaching emerged and developed. With the help of project-based teaching method, teachers can enhance their understanding of theoretical knowledge and design targeted teaching modes, so as to show the maximum effect of project-based learning and make college English teaching more smoothly. The shaping of cartoon images needs to combine language, music, props, scenes, etc., and the use of these elements needs to highlight the region. Specific cartoon characters are generally born in specific regional culture, and conversely, the image of cartoon characters can also reflect regional characteristics. Therefore, the integration of regional elements in animation can effectively promote regional culture and spread regional spirit. In this regard, Japan is very prescient. Many Japanese cartoons show Japanese national culture and characteristics in their animation works, thus achieving good communication effects. For example, Naruto and Doraemon contain Japanese food, kimono, samurai spirit, ninjutsu and so on. After watching the cartoons, many audiences will have A certain understanding of Japan, and the cartoons have enhanced the influence of Japan.